2020
DOI: 10.1101/2020.04.15.20066472
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Objective olfactory testing in patients presenting with sudden onset olfactory dysfunction as the first manifestation of confirmed COVID-19 infection

Abstract: Background: The aims of this study are to investigate the COVID-19 status of patients with initial sudden olfactory anosmia (ISOA) using nasopharyngeal swabs for RT-PCR analysis and to explore their olfactory dysfunctions with psychophysical olfactory evaluation. Methodology: This prospective study included 78 ISOA patients who fulfilled a patient-reported outcome questionnaire and underwent a nasopharyngeal swabs. Among these, 46 patients performed psychophysical olfactory evaluation using sniffing tests. Bas… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(47 citation statements)
references
References 17 publications
3
42
1
1
Order By: Relevance
“…Our study confirms and substantially extends previous reports showing that smell loss and taste loss are associated with COVID-19. Similar to other recent studies (Bagheri et al, 2020;Chen et al, 2020;Gane et al, 2020;Giacomelli et al, 2020;Haldrup et al, 2020;Hopkins et al, 2020;Lechien et al, 2020aLechien et al, , 2020bMao et al, 2020;Menni et al, 2020;Moein et al, 2020;Yan et al, 2020aYan et al, , 2020b, we find that the majority of our participants with COVID-19 reports a severe reduction in the ability to smell as compared to before the onset of that disease. Notably, this smell loss was not associated with self-reported nasal obstruction, consistent with anecdotal reports.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our study confirms and substantially extends previous reports showing that smell loss and taste loss are associated with COVID-19. Similar to other recent studies (Bagheri et al, 2020;Chen et al, 2020;Gane et al, 2020;Giacomelli et al, 2020;Haldrup et al, 2020;Hopkins et al, 2020;Lechien et al, 2020aLechien et al, , 2020bMao et al, 2020;Menni et al, 2020;Moein et al, 2020;Yan et al, 2020aYan et al, , 2020b, we find that the majority of our participants with COVID-19 reports a severe reduction in the ability to smell as compared to before the onset of that disease. Notably, this smell loss was not associated with self-reported nasal obstruction, consistent with anecdotal reports.…”
Section: Discussionsupporting
confidence: 92%
“…When psychophysical odor identification tests are used, this prevalence ranges from 76% in Europe using the Sniffin' Sticks (Lechien et al, 2020b) to 98% in Iran using the UPSIT (Moein et al, 2020), though the severity of COVID-19 in these study cohorts may not be representative of the larger population. These anecdotes, pre-prints, letters, and peer-reviewed reports (for a review see, Pellegrino et al, in press), describe chemosensory disturbances in COVID-19 with characteristics that are similar to those seen in common URIs, such as isolated sudden onset of anosmia (Gane et al, 2020), occurrence of anosmia in mild or asymptomatic cases of COVID-19 , and loss of taste (Lechien et al, 2020a;Yan et al, 2020a are rare, with the exception of two recent studies: Iravani et al (2020), assessed odor intensity in a group of Swedish respondents, while Moein et al (2020) tested a small sample of hospitalized Iranian patients with the University of Pennsylvania Smell Identification Test. We use three separate sensory modalities -smell, taste and chemesthesis -to sense our chemical environment in daily life.…”
Section: Introductionmentioning
confidence: 99%
“…In the studies that have reported it in COVID-19 tested patients, albeit from surveys, complete resolution was seen in 13% and partial resolution in 14%, with a mean time to improvement of 7.2 days (16) . This is lower than the recovery rates reported by Lechien and colleagues (15) who suggest a short term recovery rate of 44% in 59 patients who had clinically recovered from COVID-19, and also lower than the 73% that reported by Levinson and colleagues (20) , although only 15 patients make up this cohort. Recovery seems to take place within a few weeks but this may be due to short follow up and recovery may happen in others over a longer timeframe.…”
Section: Systematic Review Of the Literaturecontrasting
confidence: 63%
“…Summary findings of the included studies are in Supplemental Table 1 for Anosmia is presenting as the primary symptom or as an early symptom in patients who have tested COVID+. In a European study, 11.8% of patients reported anosmia onset before other otorhinolaryngological symptoms (15) . In the American Academy survey, 26.6% reported it as an isolated initial symptom (16) and…”
Section: Systematic Review Of the Literaturementioning
confidence: 97%
“…Nevertheless, they tend to be accompanied by rhinorrhea and nasal obstruction, which does not seem to be common in our COVID-19 sample. Similar results were found in a recent study where patients reporting sudden olfactory loss were tested for SARS-CoV-2 infection [21].…”
Section: The Role Of Questionnaires To Assess Olfactionsupporting
confidence: 89%